2019
DOI: 10.1039/c8nr08653b
|View full text |Cite
|
Sign up to set email alerts
|

Upconversion enhancement by a dual-resonance all-dielectric metasurface

Abstract: A dual-resonance all-dielectric metasurface was demonstrated to enhance the signals emitted by upconversion nanoparticles (NaYF4:Yb/Tm).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 51 publications
1
25
0
Order By: Relevance
“…Although the local field enhancement provided by dielectric nanostructures is typically smaller than that of plasmonic nanostructures, dielectric nanostructures do not suffer parasitic energy losses manifested by fluorescence quench caused by the metal's electron gas through its many internal degrees of freedom (Joule losses). Through proper design of the structure, some dielectric nanostructures can enhance the UCL of UCNPs more than 100 times [28,[41][42][43][44][45][46][47]. A variety of dielectric nanostructures, such as photonic crystals [28,[41][42][43][44], and metasurfaces [45][46][47] have been employed to enhance the UCL of UCNPs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the local field enhancement provided by dielectric nanostructures is typically smaller than that of plasmonic nanostructures, dielectric nanostructures do not suffer parasitic energy losses manifested by fluorescence quench caused by the metal's electron gas through its many internal degrees of freedom (Joule losses). Through proper design of the structure, some dielectric nanostructures can enhance the UCL of UCNPs more than 100 times [28,[41][42][43][44][45][46][47]. A variety of dielectric nanostructures, such as photonic crystals [28,[41][42][43][44], and metasurfaces [45][46][47] have been employed to enhance the UCL of UCNPs.…”
Section: Introductionmentioning
confidence: 99%
“…Through proper design of the structure, some dielectric nanostructures can enhance the UCL of UCNPs more than 100 times [28,[41][42][43][44][45][46][47]. A variety of dielectric nanostructures, such as photonic crystals [28,[41][42][43][44], and metasurfaces [45][46][47] have been employed to enhance the UCL of UCNPs. Recently, we demonstrated that the UCL of UCNPs can be enhanced more than 1000-fold by depositing UCNPs atop a resonant waveguide grating (RWG) structure, also termed 1D photonic crystal substrate, thanks to its guided mode resonance (GMR) to promote the local field of the excitation light atop the RWG [41,42].…”
Section: Introductionmentioning
confidence: 99%
“…A nowadays widely discussed approach to increase the UC efficiency is to harvest the strongly enhanced near fields in the vicinity of dielectric or plasmonic nanostructures. For photon UC with lanthanide-doped materials, several studies have been published demonstrating more than two orders of magnitude enhanced photon UC upon excitation around 980 nm using plasmonic [12] or dielectric [7,[13][14][15][16] structures. Particularly, Liang et al set a benchmark by the demonstration of five orders of magnitude enhanced UC using a dielectric superlensing array on large areas up to 50 cm 2 .…”
Section: Introductionmentioning
confidence: 99%
“…[108][109][110][111][112][113][114][115] This can be attributed to their low loss, special photonic modes, and good compatibility. [116][117][118][119][120][121][122] However, fabricating all-dielectric all-dielectric metamaterials still involves challenges. Up to now, various fabrication methods have been proposed for obtaining all-dielectric metamaterials.…”
Section: Optical All-dielectric Metamaterials Fabrication Techniquesmentioning
confidence: 99%